Supply Chain Performance Improvement Strategy through Quality of Synergy in the Automotive Components Industry - Tri Purwani; Lutfi Nurcholis (Jurnal Dinamika Manajemen)
The purpose of this study were 1) develop a new concept of Bilateral Symmetry, which is the ability of similarity based on transparency and standardization, 2) conduct empirical testing and analyzing the effect of bilateral symmetry to the improved supply chain performance through quality of synergy in industrial automotive components. The study population includes the entire automotive component industry in Indonesia. This study used sample of 105 respondents using purposive sampling method to comply with the AMOS program. The study result shows that the ability of similarity standardization and the ability of the similarity of transparency have positive significant impact on the quality of synergy, and quality of synergy have positive significant impact on the supply chain performance. In addition, from the results of hypothesis testing found two strategies that can improve supply chain performance with 1) increasing the ability of similarity standardization and 2) improve transparency through quality of synergy.